Selection of Stable Housekeeping Gene for Quantitative Real-time PCR (qRT-CR) Analysis in Human Normal and Cancerous Tissues - Lasim, Masniza Muhamad (Universiti Sains Malaysia, 2014)
Gene therapy is one of the new developed technology that uses genes to treat cancer illness whilst quantitative real-time polymerase chain reaction (qRT-PCR) is the most frequently approached method to study about the cancer gene expression for gene therapy application. Housekeeping gene (HKG) is an internal control gene used to normalize the parameter of qRT-PCR in order to obtain reliable quantitative gene expression measures. Selection of a suitable HKG is essential in every experiment involved qRT-PCR analysis. In this study, the aim was to select the stable HKGs in qRT-PCR analysis using different cell types (normal brain SVG-pl2 vs cancerous brain DBTRG-05MG) and different tissue types (brain cancer DBTRG-05MG vs urinary bladder cancer T24). RNA was extracted from these cell lines using RNeasy® Mini Kit. Then, cDNA was synthesized using RevertAid H Minus First Strand cDNA Synthesis Kit. The qRT-PCR was performed using Applied Biosysteins machine (ABI7500) and the data obtained was analyzed by Normfinder and Bestkeeper. In the beginning, seven candidate HKGs [TATA box binding protein (TBP), beta-actin (ACTB), gIyceraldehydes-3-phosphate dehydrogenase (GAPDH), hypoxanthine phosphoribosyl-transferase (HPRT), ribosomal protein large Pl (RPLP1), eukaryotic initiation factor 4A (E1F4A) and tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein, zeta polypeptide (YWHAZ)] were evaluated in this study. However, ACTB showed primer dimer formation and was removed from further analysis. Analysis from Normfinder and Bestkeeper had selected TBP as the most stable gene while RPLP1 and HPRT were ranked as the least stable genes. Normalization of PKM2 mRNA expression was performed by 2 AACT method using these genes as reference genes. The result showed 3.02-fold and 3.23-fold change in DBTRG-05MG and T24 respectively, compared to normal control, SVG-pl2 when normalized to TBP. Normalization to different HKGs gave different relative PKM2 mRNA levels. To verify this result, protein analysis such as Western blot and ELISA were recommended. In conclusion, a valid HKG is essential to get reliable quantitative expression data. TBP was selected as the most stable HKG while HPRT and RPLP1 were the least HKGs in this study.